Is there impact of the SARS-CoV-2 pandemic on steroidogenesis and fertility? - Knížatová, N; Massányi, M; Roychoudhury, S; Guha, P; Greifová, H; Tokárová, K; Jambor, T; Massányi, P; Lukáč, N (Physiological research, 2021)
In December of 2019, several cases of unknown atypical respiratory diseases emerged in Wuhan, Hubei Province in China. After preliminary research, it was stated that the disease is transmittable between humans and was named COVID-19. Over the course of next months, it spread all over the world by air and sea transport and caused a global pandemic which affects life of everyone now-a-days. A large number of countries, have since been forced to take precautions such as curfews, lockdowns, wearing facemasks etc. Even with vaccines being produced in mass numbers, lack of targeted therapy continues to be a major problem. According to studies so far it seems that elderly people are more vulnerable to severe symptoms while children tend to by asymptomatic or have milder form the disease. In our review, we focused on gathering data about the virus itself, its characteristics, paths of transmission, and its effect on hormone production and secretion. In such, there is insufficient information in the literature worldwide, especially the ones that focus on the effect of COVID-19 on individual organs systems within the human body. Hence, the present evidence-based study focused on the possible effects of COVID-19 on adrenal gland and gonads i.e. on the process of steroidogenesis and fertility.
Keywords: Gonads; nadledviny; Steroids; fertilita; Fertility; Host-Pathogen Interactions; steroidy; Animals; lidé; SARS-CoV-2; Adrenal Glands; interakce hostitele a patogenu; Humans; zvířata; COVID-19; gonády